Risk of cardiovascular diseases in women with a spontaneous abortion in anamnesis - Siusiuka, V. H.; Demidenko, O. V.; Deinichenko, O. V.; Onopchenko, S. P.; Bondarenko, S. A.; Сюсюка, Володимир Григорович; Деміденко, Олександр Вікторович; Дейніченко, Олена Валеріївна; Онопченко, Світлана Павлівна; Бондаренко, Сергій Анатолійович (My University, 2023)
An estimated 15% of pregnancies end in miscarriage. Miscarriage can lead to serious morbidity, including haemorrhage, infection, and even death, particularly in settings without adequate healthcare provision.